2015
DOI: 10.1002/ajmg.a.36958
|View full text |Cite
|
Sign up to set email alerts
|

Mosaic trisomy 15 in a liveborn infant

Abstract: With only a small number of cases in the medical literature, mosaic trisomy 15 in liveborn infants is very rare. Despite its rarity, similar features among individuals have been described, including intrauterine growth retardation, craniofacial abnormalities and facial dysmorphisms, cardiac disease, and other organ anomalies. Very few liveborns have survived the first year of life. We report here on a term infant with growth restriction and multiple congenital anomalies who was found to have mosaic trisomy 15.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
10
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 19 publications
(10 citation statements)
references
References 19 publications
0
10
0
Order By: Relevance
“…The features of mosaic trisomy 15 have been described previously, and mainly include intrauterine growth retardation, cardiac diseases, craniofacial dysmorphisms, and other organ anomalies. 18,19 In this case, no fetal structural anomaly was detected by ultrasound scans until 24 weeks' gestation. Clinical follow-up showed that this pregnancy was ended by the patient's choice.…”
Section: Discussionmentioning
confidence: 65%
“…The features of mosaic trisomy 15 have been described previously, and mainly include intrauterine growth retardation, cardiac diseases, craniofacial dysmorphisms, and other organ anomalies. 18,19 In this case, no fetal structural anomaly was detected by ultrasound scans until 24 weeks' gestation. Clinical follow-up showed that this pregnancy was ended by the patient's choice.…”
Section: Discussionmentioning
confidence: 65%
“…Mosaic trisomy 15 appears to be a rare condition in liveborn children and fetuses. The features of mosaic trisomy 15 have been described in approximately 10 reports in the published literature . Two liveborn infants with complete trisomy 15 have been described .…”
Section: Discussionmentioning
confidence: 99%
“…The features of mosaic trisomy 15 have been described in approximately 10 reports in the published literature. 4,5 Two liveborn infants with complete trisomy 15 have been described. 2,3 However, mosaic trisomy 15 may be overlooked due to low levels of mosaicism.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations